Historical Empathy for effective teaching and meaningful learning in secondary students in educational units in Chile (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2026)
The study evaluated the impact of historical empathy as a pedagogical strategy to promote meaningful learning in history, geography, and social sciences among secondary school students in Chile. A quantitative methodology was applied using a pre-experimental design with 43 secondary school students from educational institutions in Chile. The IRI Scale was used as an instrument for both the pre- and post-tests of the educational intervention. The results show differences in three of the dimensions (perspective taking, fantasy and personal distress) measured by the IRI scale, recognizing that students can engage in debate without applying value judgments, feel more connected to historical figures, and respond by considering the emotions of the historical context during the interventions. It is concluded that historical empathy promotes critical understanding of the past and ethical-civic competencies.
Keywords: historical empathy; effective teaching; meaningful learning